2001
DOI: 10.1111/j.1469-8749.2001.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Is increased D2 receptor availability associated with response to stimulant medication in ADHD

Abstract: The purpose of this study was to estimate striatal dopamine (D2) receptor availability in non-drug treated children with attention-deficit-hyperactivity disorder (ADHD) before and after methylphenidate therapy, and to examine correlations between severity of symptoms and response rates to stimulant medication with levels of striatal D2 receptor binding. Nine children (six males, three females; mean age 9.8 years, SD 2.3 years) with ADHD participated. All underwent iodobenzamide (123I IBZM) brain SPECT within 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In the imaging studies, various parameters of the dopaminergic system have been measured, including DAT (Spencer et al, 2005), dopamine D 2 receptors (Lou et al, 2004), dopamine synthesis (Ernst et al, 1999), and extracellular dopamine levels (Ilgin, Senol, Gucuyener, Gokcora, & Sener, 2001). The most widely investigated parameter has been the DAT, especially variations in the density of presynaptic DATs.…”
Section: Introductionmentioning
confidence: 99%
“…In the imaging studies, various parameters of the dopaminergic system have been measured, including DAT (Spencer et al, 2005), dopamine D 2 receptors (Lou et al, 2004), dopamine synthesis (Ernst et al, 1999), and extracellular dopamine levels (Ilgin, Senol, Gucuyener, Gokcora, & Sener, 2001). The most widely investigated parameter has been the DAT, especially variations in the density of presynaptic DATs.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ADHD with higher striatal dopamine transporter availability show a better response to methylphenidate treatment [15]. Further, striatal dopamine receptor (D2) availability is positively associated with methylphenidate response [73]. In parallel, larger GM volumes are believed to be related to an increased density of neurons and more synapses in the local brain region [74].…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted with humans found that risperidone pretreatment attenuated discriminative-stimulus effects of d-amphetamine and some self-reported behavioural effects (Rush et al, 2003), which may be considered as already-existing evidence of altered stimulant response after atypical antipsychotic exposure. Recent evidence by SPECT imaging suggests that, in children with ADHD, a positive clinical response with methylphenidate corresponds to down-regulation of the post-synaptic dopamine receptors and down-regulation of the dopamine transporter in the striatal system (Ilgin et al, 2001;Moll et al, 2001;Vles et al, 2003). In contrast, atypical neuroleptics up-regulate dopamine receptors (Silvestri et al, 2000;Tarazi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%